L2 English derivational knowledge: Which affixes are learners more likely to recognise? - Leontjev, Dmitri (Studies in Second Language Learning and Teaching, 2016)
Knowledge of derivational morphology is considered an important aspect of vocabulary knowledge both in L1 (mother tongue) and L2 (second or foreign language) English language learning. However, it is still not clear whether different derivational affixes vary in their (learning) difficulty. The present study examines whether Bauer and Nation’s (1993) teaching order of L2 English affixes can account for the difficulty learners have with recognising the affixes. The participants in the study were L1 Estonian and Russian learners of English at upper-secondary schools in Estonia (n = 62). Their performance was measured on a word segmentation task. There were significant differences in the number of affixes the learners were able to successfully recognise at different levels, as classified by Bauer and Nation (1993). By and large, with the exception of no significant difference between Level 5 and Level 6 affixes, the higher the affix level was, the less likely the learners were to recognise the affixes at this level. I argue that these results can support the order proposed by Bauer and Nation. The implications of the finding for teaching and further research are also discussed.